KUALITAS PELAYANAN PUBLIK BIDANG ADMINISTRASI KEPENDUDUKAN DI KANTOR DINAS KEPENDUDUKAN CATATAN SIPIL KAB. BANTAENG - Naldi, Muh; Mahsyar, Abdul; Yahya, Muhammad (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
This study aims to examine the quality of public services in the field of population administration in Bantaeng district by using the theory of service quality. Public services are interesting to observe because their activities are in the context of fulfilling the basic needs of citizens for goods or services and administrative services related to the public interest. There are four qualities of public services including, direct evidence (tangibles), reliability (Reliability), responsiveness (responsiveness), assurance (assurance).